Sulodexide improves vascular permeability via glycocalyx remodelling in endothelial cells during sepsis - Ying, Jiayun; Zhang, Caiyan; Wang, Yaodong; Liu, Tingyan; Yu, Zhenhao; Wang, Kexin; Chen, Weiming; Zhou, Yufeng; Lu, Guoping (Frontiers in Immunology, 2023)
Background Degradation of the endothelial glycocalyx is critical for sepsis-associated lung injury and pulmonary vascular permeability. We investigated whether sulodexide, a precursor for the synthesis of glycosaminoglycans, plays a biological role in glycocalyx remodeling and improves endothelial barrier dysfunction in sepsis. Methods The number of children with septic shock that were admitted to the PICU at Children’s Hospital of Fudan University who enrolled in the study was 28. On days one and three after enrollment, venous blood samples were collected, and heparan sulfate, and syndecan-1 (SDC1) were assayed in the plasma. We established a cell model of glycocalyx shedding by heparinase III and induced sepsis in a mouse model via lipopolysaccharide (LPS) injection and cecal ligation and puncture (CLP). Sulodexide was administrated to prevent endothelial glycocalyx damage. Endothelial barrier function and expression of endothelial-related proteins were determined using permeability, western blot and immunofluorescent staining. The survival rate, histopathology evaluation of lungs and wet-to-dry lung weight ratio were also evaluated. Results We found that circulating SDC1 levels were persistently upregulated in the non-alive group on days 1 and 3 and were positively correlated with IL-6 levels. Receiver operating characteristic curve analysis showed that SDC1 could distinguish patients with mortality. We showed that SDC1-shedding caused endothelial permeability in the presence of heparinase III and sepsis conditions. Mechanistically, sulodexide (30 LSU/mL) administration markedly inhibited SDC1 shedding and prevented endothelial permeability with zonula occludens-1 (ZO-1) upregulation via NF-κB/ZO-1 pathway. In mice with LPS and CLP-induced sepsis, sulodexide (40 mg/kg) administration decreased the plasma levels of SDC1 and increased survival rate. Additionally, sulodexide alleviated lung injury and restored endothelial glycocalyx damage. Conlusions In conclusion, our data suggest that SDC1 predicts prognosis in children with septic shock and sulodexide may have therapeutic potential for the treatment of sepsis-associated endothelial dysfunction.